Determination of The Correlation of Job Stress and Burnout Levels of Nurses with Their Job and Life Satisfaction Levels - Gazi BARAN CAMCİ; Esin KAVURAN (Atatürk University, 2021)
Aim: This study was conducted with descriptive and cross-sectional design to determine the correlation between the job stress, burnout, job and life satisfaction levels of nurses. Methods: The study was carried out in public hospital between September-November 2020. It was aimed to reach the all population, no sampling method was used. The data were collected from 642 voluntary nurses using the Descriptive Characteristics Form, Perceived Stress, Maslach Burnout Inventory, Nurse Job Satisfaction, and Satisfaction with Life. Frequency, percentage, mean and standard deviation values, ANOVA test, t-test, Mann-Whitney U test and correlation analysis were used to assess data. Results: It was determined that there was a positive weak and significant correlation between the Maslach Burnout Inventory and Perceived Stress Scale of the nurses and a negative weak and significant correlation between the Satisfaction with Life Scale and Job Satisfaction Scale (p<0.05). It was determined that there was a negative weak and significant correlation between the Job Satisfaction and Perceived Stress and a positive moderate and significant correlation between the Job Satisfaction and the Satisfaction with Life. There was a negative weak and significant correlation between the Satisfaction with Life Scale and Perceived Stress. Conclusion: It was determined that a positive significant correlation between job stress and burnout and a negative significant correlation between the two present variables and job-life satisfaction.